2019
DOI: 10.1177/1747954119887301
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and mid-season repeated sprint ability of soccer referees from the first and second divisions

Abstract: The main aim of the study was to investigate the differences in repeated sprint ability of first- compared to second-division referees at the beginning and in the middle of the soccer season. Twenty-seven main and 51 assistant referees, from the first (age 36.2 ± 5.3) and the second (age 28.8 ± 3.9) soccer divisions, performed two fitness tests—at the beginning and at mid-season, consisting of a repeated sprint test of 6 × 40 m and 5 × 30 m sprints for the referees and assistant referees, respectively. While n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In this respect, another study analyzed the first vs. second-division soccer referees and found higher values for the second division over the first referees regarding repeated sprint ability. The study justified such results with the higher level of experience of first-division referees that probably used better anticipation and pitch positioning, improved decision-making skills, and economical movement patterns, which consequently decreased the need of producing more sprints during competition (Meckel et al, 2020 ). For the previous reasons, it is expected that body composition differences between the first and second divisions could exist although no studies could be found in this regard.…”
Section: Introductionmentioning
confidence: 60%
“…In this respect, another study analyzed the first vs. second-division soccer referees and found higher values for the second division over the first referees regarding repeated sprint ability. The study justified such results with the higher level of experience of first-division referees that probably used better anticipation and pitch positioning, improved decision-making skills, and economical movement patterns, which consequently decreased the need of producing more sprints during competition (Meckel et al, 2020 ). For the previous reasons, it is expected that body composition differences between the first and second divisions could exist although no studies could be found in this regard.…”
Section: Introductionmentioning
confidence: 60%
“…Currently, most football science studies are based on the physical performance profiles of athletes while fewer studies have focused on referees [ 6 , 7 ]. In elite football, a match cannot take place without the participation of the referees, but their profiles have not been widely investigated [ 8 ].…”
Section: Introductionmentioning
confidence: 99%